2020
DOI: 10.15587/1729-4061.2020.193985
|View full text |Cite
|
Sign up to set email alerts
|

A semi-analytical method for analys of contact interaction between structural elements along aligned surfaces

Abstract: Значна частина конструкцій має у своєму складі деталі, які перебувають у контактній взаємодії одна з одною. Це, наприклад, штампи, прес-форми, верстатні пристосування, технологічне обладнання, двигуни тощо. Для них характерним є варійований режим навантаження. Тому важливим аспектом при дослідженні напружено-деформованого стану таких конструкцій є визначення залежності контактного тиску від зовнішніх сил, які на них діють. Принцип суперпозиції для контактних задач у загальному випадку незастосовний. Однак для … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The research methodology extends the approach proposed in [28]. It was applied to analyze contact interaction between the spherical piston and toroidal running track on the stator of a hydrovolumetric drive GOP-900 [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research methodology extends the approach proposed in [28]. It was applied to analyze contact interaction between the spherical piston and toroidal running track on the stator of a hydrovolumetric drive GOP-900 [3].…”
Section: Methodsmentioning
confidence: 99%
“…It may be concluded that adequate analysis of contact interaction with intermediate layers requires a rigorous combination of micro and macro models. An approach that implements such integration of the two models was proposed in [28]. The application of FEM or BEM governs the macrolevel while the microscopic response is represented as an effective Winkler layer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed criterion allows evaluating the technical level of hydraulic devices, depending on their design and operational parameters. It can be done at the CAD (Computer-aided design) stage [46]- [49]. This criterion is based on common methodological principles based on the data given in the relevant directories or technical specifications for the design of the product.…”
Section: Definitive Assessment Criterion Of Technical Levelmentioning
confidence: 99%